Characterization and photocatalytic properties of CdS nanowires synthesized by reflux-assisted solvothermal method - A. Phuruangrat (2019)
© 2019, S.C. Virtual Company of Phisics S.R.L. All right reserved. CdS nanowires were synthesized by reflux-assisted solvothermal method. The phase and morphologies of as-synthesized CdS samples were investigated by X-ray powder diffraction (XRD), Raman spectrophotometry and transmission electron microscopy (TEM). The results show that the product synthesized by the 160 °C and 24 h reflux-assisted solvothermal method was hexagonal CdS nanowire with aspect ratio of >300. The photocatalytic reaction of as-synthesized CdS samples was investigated by photodegradation of methyl orange (MO) and rhodamine B (RhB) under visible light irradiation. They were found that CdS nanowires showed photocatalytic degradation of 99.66% for MO and 93.63% for RhB within 60 min under visible light.